The Effect Of Cat Stretch Exercise Technique On Dysmenorrhea In Female Students - Dana Apirda; Sri Martini; Nesi Novita; Rina Nursanti (Journal of Maternal and Child Health Sciences (JMCHS), 2023)
Cat Stretch Exercise is a gymnastics technique aimed at improving blood circulation, enhancing muscle and joint strength, and increasing the level of endorphin hormone in the blood, which can reduce menstrual pain. To determine the effect of Cat Stretch Exercise technique on dysmenorrhea in female students of SMA Negeri 22 Palembang, in 2023. This study employed a quantitative study with pre-experimental method. The research design is One Group Pretest-Posttest, with purposive sampling. Based on the statistical analysis using the Wilcoxon test, the ρ value was 0.033 (α ≤ 0.05). This indicates that there is a significant influence between the independent variable (Cat Stretch Exercise technique) and the dependent variable (menstrual pain), hence H1 is accepted, meaning that there is an effect of Cat Stretch Exercise technique on the reduction of menstrual pain in female students of SMA Negeri 22 Palembang. There is an effect of Cat Stretch Exercise technique ondysmenorrhea in female students of SMA Negeri 22 Palembang.